Effectiveness Of Green Open Space Policy As A Public Space In Makassar City - Mohammad Yunus; Dedy Herianto; Rahman Rahman (Public Resource Innovation Management and Excellence, 2025)
The problem discussed in this study is how effective is the Green Open Space policy as a public space in Makassar City?. This type of research is descriptive with a qualitative approach. The informants were leaders and staff of the Makassar City Living Environment Office and the community who used Green Open Space as many as 9 people. The results of the study show that the policy of providing Green Open Space in Makassar City is only available at 11.47% consisting of public Green Open Space of 6.60% and 4.87% of private Green Open Space, meaning that the Makassar City Government still needs 18.53% to meet 30% of the city area according to Law No. 26 of 2007 Article 29, so it is said to be less effective. So that its function as a center for community interaction is less effective because it has not been fully fulfilled, especially facilities for people with disabilities and children. Likewise, the function as the lungs of the city is less effective, it is evident that the Makassar City Air Quality Index (AQI) is 89% included in the medium category (51-100) close to unhealthy. The function as an Open Space for the Community, especially for sports activities, short discussion activities and brief meetings is quite good, or it can be said that it is quite effective. Likewise, Green Open Space as a place of business is quite effective, such as in the Losari Green Open Space, Karebosi Pakui Sayang A.P. Pettarani, Hertasning, especially Micro, Small and Medium Enterprises. In order for this research to be useful for the Makassar City Government, it is recommended to the Makassar City Government Environment Agency to strive to fulfill the Green Open Space quota of 30% of the city area or at least 20%, therefore the mandate of the law, strive to fulfill the Green Open Space facilities and maintain the existing ones so that they are not abused by the bad community, for example, criminal groups.